Neurological Pain Study in Animals with Proposed Analgesic Mechanism Profiles - Chuan Wei Oo; Yean Chun Loh; Mun Fei Yam; Rusliza Basir (Technological Innovation in Pharmaceutical Research Vol. 7, 2021)
Pain is the most natural sensation in our body that plays a vital protecting role of all organisms against severe harm. It is the most complicated topic in neurological study of all time and yet there has none of scientist clearly justify all the mechanisms mediated by pain receptors. Of course there have been some answers to curbing of pain which is a life-saver in numerous situations - chronic and acute pain conditions alike. This has been explored by scientist using pain-like behavioral study methodologies in concious animals since decades ago to characterize the analgesic profile for pain regulation development. However, widely the methodology is being practiced, there has rarely been a complete review of all these methodology, their benefits and its downside coupled with the mechanism of action that is involved. Thus, this topic solely focused on the complete protocol that is being adapted in each animal’s “pain-like” behavioural study that induced by analgesic agents, the different assessment method used for inflammatory pain and the mechanistic actions underlying each behavioral study methodology. This comprehensive discussion will significantly provide a concise idea and improve our scientists’ understanding towards the pain management.